Pengaruh Model Pembelajaran Kooperatif Tipe TPS dalam Meningkatkan Hasil Belajar PPkn Siswa SD - Eka Resti Barus (Program Studi PGSD Kampus UPI di Serang, 2020)
The purpose of this study was to determine whether the use of the think-pair-share (TPS) learning model can increase the activities and learning outcomes of elementary school students' PPKN. This was done because before using the think-pair-share (TPS) learning model there was a score gap between students who received high scores and students who scored below the KKM, namely 70. This type of research was a quasi-experimental study, totaling 24 students. The instrument for collecting data on learning outcomes of PPKn using learning outcomes tests and the instrument for collecting data on learning activities is observation sheets. The results showed that the class average initial ability test score was only 57.5 with class completeness of 20.83% and students who scored ≥ 70 were 5 students. In the implementation of the pretest, the class average score was 67.91 and grade completeness 45.83% and students who obtained a value> 70 were 11 students. Furthermore, in the posttest there was an increase in the class average to 75.20 and class completeness to 83.33% (an increase of 37.5%) and students who obtained a grade of> 70 were 20 students. Based on these results, it can be concluded that the TPS learning model can improve the activities and learning outcomes of PPKn class V SD Negeri 105269 Sei Beras Sekata